2021
DOI: 10.1088/1755-1315/779/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mixing rice with mung bean in different food meals on postprandial blood glucose level in healthy adults

Abstract: Rice is known as carbohydrate rich food and may tend to increase blood glucose levels rapidly. This work was designed to mix rice grains with mung beans to control releasing blood glucose and to keep a normal blood sugar level. Five food meals of rice and mung bean were prepared. The first meal was just 100% cocked rice, the second was 75% rice and 25% mung bean, the third was 50% rice and 50% mung bean, the fourth was 25% rice and 75 % mung bean and the fifth was 100% mung bean. 25 volunteers aged between 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
2
1
0
1
Order By: Relevance
“…The results of present study are in agreement with the findings of Durgarao (2017) in rice and green gram based khichdi. Similar results have also been reported by Basim et al (2021), who observed decrease in crude fat content in rice and mungbean based food meal.…”
Section: Crude Fatsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of present study are in agreement with the findings of Durgarao (2017) in rice and green gram based khichdi. Similar results have also been reported by Basim et al (2021), who observed decrease in crude fat content in rice and mungbean based food meal.…”
Section: Crude Fatsupporting
confidence: 91%
“…With the incorporation of instant dehulled mungbean, the crude fibre content increased which might be due to the presence of higher crude fibre content in instant dehulled mungbean. Similar findings have been reported by Bazaz et al (2016) in complementary foods made from rice and green gram flour, Jan et al (2018) in rice and mungbean based weaning food and Basim et al (2021) in rice and mungbean based food meal.…”
Section: Crude Fibresupporting
confidence: 87%
“…[20] Mung bean protein had an inhibitory impact on insulin resistance, [21] and in healthy people, meals containing Mung beans also shown a drop in postprandial blood sugar levels. [23] Likewise, fermented Mung bean extracts have demonstrated superior antihyperglycemic action, which might be attributed to their higher GABA concentration and free amino acid content. [26] Additionally, studies have extracted and identified the Mung bean's active peptides, which have been shown to enhance glucose absorption and clarify how they work in L6 myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…Jenis bahan baku dengan kombinasi kacang-kacangan yang digunakan menjadi faktor dalam perolehan kadar protein. Hal ini sejalan daengan penelitian multigrain rice yang dilakukan oleh (Basim et al, 2021) dengan kadar protein sebesar 8,29% pada formulasi serealia 75% dan kacang-kacangan 25%. Sedangkan pada konsentrasi serealia 25% dan kacang-kacangan 75% diperoleh kadar protein sebesar 15,98%.…”
Section: Proteinunclassified